2019
DOI: 10.1002/cplu.201900625
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Like Catalytic Activity of Porphyrin‐Functionalized Ceria Nanotubes for Water Oxidation

Abstract: Artificial enzymes have broad applications in catalysis and can be used to help understand catalytic mechanisms. Nanoceria has various enzyme‐mimetic properties that depend on the relative content of Ce3+ and Ce4+. In this context, CeO2 nanotubes was investigated as catalase mimics for water oxidation. The photosensitizer 5,10,15,20‐meso‐tetra(4‐carboxyphenyl) porphyrin (TCPP) was facilely embedded in CeO2 nanotubes (TCPP@CeO2 NTs), and photoinduced charge transfer was shown to occur between the strongly coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Moreover, the chiral molecule coating also prevented the production of H2O2 in neutral and acidic conditions that favor the reaction pathway towards H2O2 (Figure 3b). This study inspired several other attempts [34,35,36] to use the CISS effect to boost the OER, including using catalysts consisting of layered transition metal chalcogenides [37] . Recently, Pan et al demonstrated that tuning the electron spin polarization in titanium dioxide by changing the density of metal vacancies can improve its photocatalytic activity [38] .…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 61%
“…Moreover, the chiral molecule coating also prevented the production of H2O2 in neutral and acidic conditions that favor the reaction pathway towards H2O2 (Figure 3b). This study inspired several other attempts [34,35,36] to use the CISS effect to boost the OER, including using catalysts consisting of layered transition metal chalcogenides [37] . Recently, Pan et al demonstrated that tuning the electron spin polarization in titanium dioxide by changing the density of metal vacancies can improve its photocatalytic activity [38] .…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 61%
“…Moreover, the chiral molecule coating also prevented the production of H 2 O 2 in neutral and acidic conditions that favor the reaction pathway towards H 2 O 2 (Figure 3b). This study inspired several other attempts [34,35,36] to use the CISS effect to boost the OER, including using catalysts consisting of layered transition metal chalcogenides [37] . Recently, Pan et al.…”
Section: Ciss In Electrocatalytic Reactionsmentioning
confidence: 68%
“…The ability of nanosized ceria to promote the formation of radical oxygen species has been exploited in photocatalytic water oxidation, too [ 15 , 108 ]. For instance, a porphyrin photosensitizer was embedded in ceria nanotubes so that the electronic communication between the two components allowed for the enhanced production of molecular oxygen over the competing hydrogen peroxide generation from the partial water oxidation [ 109 ]. Nanosized ceria was also reported to enhance the performance of microbial fuel cells by creating oxygen reservoirs for the oxygen reduction reaction (ORR), while direct involvement of the cerium redox couple in the catalysis was only marginal [ 110 ].…”
Section: (Bio)applicationsmentioning
confidence: 99%